2009
DOI: 10.1175/2008jcli2649.1
|View full text |Cite
|
Sign up to set email alerts
|

El Niño Impacts on Precipitation in the Western North Pacific–East Asian Sector

Abstract: In this study, the western North Pacific–East Asian (WNP–EA) rainfall anomaly induced by the strong El Niño in 1982–83, 1991–92, and 1997–98, and its association with the mean state, are examined. Over the northern part of the WNP–EA region (north of 20°N), which is dominated by southwest–northeast tilting frontal systems, positive rainfall anomalies from the fall before the El Niño peak phase (year 0) to the first wet period after the peak phase (year 1) are affected by low- and midlevel horizontal moisture c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 59 publications
1
39
0
Order By: Relevance
“…This result is an increase in precipitation over the whole EASM region in this model experiment. Circulation anomalies in the Philippine Sea tend to appear in conjunction with changes to the Pacific SSTs, affecting precipitation rates in East Asia (e.g., Wang et al 2000;Watanabe and Jin 2002;Chou et al 2009). The Philippine Sea anticyclonic anomaly (Fig.…”
Section: El Niño-southern Oscillationmentioning
confidence: 99%
“…This result is an increase in precipitation over the whole EASM region in this model experiment. Circulation anomalies in the Philippine Sea tend to appear in conjunction with changes to the Pacific SSTs, affecting precipitation rates in East Asia (e.g., Wang et al 2000;Watanabe and Jin 2002;Chou et al 2009). The Philippine Sea anticyclonic anomaly (Fig.…”
Section: El Niño-southern Oscillationmentioning
confidence: 99%
“…It can therefore be proposed that the recent climatic change might have caused the spawning sites of A. japonica to be frequently shifted southward, and subsequently, the glass eel recruitment along the Kuroshio decreased, while the numbers entering southern areas such as northern Luzon Island may have increased. Global atmospheric changes that have caused frequent El Niño events reduced precipitation in the tropical region (Chou et al 2009). The salinity front that is a landmark to determine the spawning site of Japanese eels in the North Equatorial Current (Aoyama et al 2014) then moved southward due to a reduction of the low-salinity water supply by rainfall to the ocean surface.…”
Section: A Japonica In Northern Luzon Islandmentioning
confidence: 99%
“…Advances in remote sensing have provided us with long-term and globally complete satellite-gauge-merged precipitation products and satellite-based estimates, such as the Global Precipitation Climatology Project (GPCP) [8], the Climate Prediction Center Merged Analysis of Precipitation (CMAP) [9], and the Tropical Rainfall Measuring Mission (TRMM) Multi-satellite Precipitation Analysis (TMPA) [10]. Many studies have investigated the impacts of ENSO on precipitation using these satellite-based precipitation datasets [11][12][13][14][15][16]. For example, Dai and Wigley [11] and Haddad et al [14] derived the global climatology and variability of ENSO-induced precipitation using the CMAP and TRMM datasets, respectively, and found that ENSO is the major driver of the interannual variability of global rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…For example, SST anomalies, which are the expression of ENSO events and the response to evaporation and downward solar radiation, are generally observed positively correlated with precipitation in the tropics [15,23,24]. Precipitation variability is also generally proportional to wind speed variability associated with ENSO; high wind speeds are associated with higher evaporation and latent heat flux from the ocean to the atmosphere [15,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation